Bored out of our minds. (2nd May 2023) - Brown, Paula
Abstract : Paula Brown, early years teacher and play therapist, considers whether boredom is a wholesome precursor to creativity or a dangerous force which should be banished from early years settings, and how practitioners can use children's boredom and work with it constructively.